Experimental and simulation study of tensile strength of banana and glass fibres and their hybrid epoxy composites - Nordin, Mustafa; Aziz, Mohd Rozaiman; Othman, Rozaini (Smart Manufacturing Research Institute (SMRI), 2025)
In recent years, the growing emphasis on sustainability has driven researchers to explore eco-friendly materials that can provide sufficient mechanical strength while minimizing environmental impact. Composite materials have gained prominence for their ability to combine the advantageous properties of different constituents. In particular, hybrid composites composed of multiple fibre types offer potential for use in demanding industries such as aerospace and automotive manufacturing. Although fibreglass and epoxy are widely recognized for their excellent mechanical performance, the integration of natural fibres such as banana fibre in hybrid composites remains limited. Previous studies have also revealed a notable lack of simulation-based research focusing on banana fibre reinforcement, whether as a standalone material or in combination with fibreglass. Therefore, this gap highlights the need to further investigate and validate the mechanical performance of banana-glass fibre composites through both experimental and simulation approaches. This study aims to determine the optimal tensile properties of glass fibre and banana fibre composites with various layer configurations and validate the simulation results against experimental findings to ensure the accuracy and reliability of the modelling approach. The composites were fabricated using the hand lay-up method and evaluated through tensile testing and simulation. The findings showed that the L1 configuration, composed entirely of glass fibre, exhibited the highest tensile strength, recording an ultimate load of 5.96 kN and an ultimate stress of 119.46 MPa experimentally, while simulation results yielded 5.83 kN and 119.06 MPa. In contrast, the L2 configuration, made solely of banana fibre, showed the lowest tensile performance, with an ultimate load of 1.13 kN and ultimate stress of 10.17 MPa experimentally, compared to 1.11 kN and 9.84 MPa in simulation. Among the hybrid laminates, L4 (5 glass fibre layers and 4 banana fibre layers) outperformed L3 (4 glass fibre layers and 5 banana fibre layers), attributed to its layer arrangement that enhanced structural integrity. The percentage error between experimental and simulated results was below 4%, confirming strong correlation and model accuracy. Both research objectives were successfully achieved. The results demonstrated that glass fibre significantly enhances the tensile strength of hybrid composites, while banana fibre contributes to environmental sustainability with moderate strength retention. Overall, the study validates the feasibility of using banana–glass fibre hybrid composites and supports their potential application in lightweight, sustainable engineering materials. The first objective, which aimed to determine the optimal tensile properties of glass fibre and banana fibre in various configurations by adjusting their layer arrangements, was successfully achieved. The second objective, focused on validating the tensile properties obtained from simulation results against experimental findings, was also successfully fulfilled where the percentage error was below percentage error of 4%. The results indicate that the laminate composed entirely of glass fibre layers (L1) exhibited the highest tensile properties, whereas the laminate consisting solely of banana fibre layers (L2) demonstrated the lowest tensile strength. In the case of hybrid composites, glass fibre contributed a significantly greater effect on the overall strength compared to banana fibre alone. Among the hybrid laminates, L4 achieved higher ultimate load and ultimate stress than L3, which could be attributed to its lay-up configuration where two glass fibre layers were positioned between two banana fibre layers, thereby enhancing the structural integrity of the composite.